What Explains Variability in Blood Pressure Readings? Multilevel Analysis of Data from 8,731 Older Adults in 20 Ontario Communities - O'Rielly, Susan (Université d'Ottawa / University of Ottawa, 2011)
Title: What explains variability in blood pressure readings? Multilevel analysis of data from 8,731 older adults in 20 Ontario Communities Objectives: Despite universal healthcare and drug coverage for adults aged 65 and over in Ontario, hypertension, a treatable condition, remains uncontrolled among many older adults. Moreover, there are geographic disparities in blood pressure and hypertension within and across Canadian provinces and territories. Using baseline data collected on 8,731 older adults participating in the Cardiovascular Health Awareness Program (CHAP) in 20 randomly selected Ontario communities, we investigated associations between systolic blood pressure (SBP) and individual- and community-level characteristics, controlling for self-reported use of blood pressure medications. Method: Older adults were recruited via invitation by local family physicians, public advertising and word of mouth to attend community pharmacy sessions. During the sessions, trained older adult volunteers assisted participants to complete a cardiovascular disease risk factor questionnaire and blood pressure assessments using an automated blood pressure measuring device. The Postal Code Conversion File Plus was used to confirm residence within one of the 20 study communities. A multilevel linear regression analysis with participants nested within communities was used to determine which individual- and/or community-level characteristics were associated with measured systolic blood pressure level controlling for self-reported use of blood pressure medication. Results: 4,706 participants (53.9%) reported the use of blood pressure medication. Mean systolic blood pressure (SBP) levels varied among the 20 communities from 128.1 mmHg to 134.7 mmHg for participants not using blood pressure medication and from 131.9 mmHg to 139.0 mmHg for participants using blood pressure medication. The intraclass correlation coefficients were very small: less than 0.2% of the total variance was between communities. Among participants not using blood pressure medication, SBP was associated with the following individual- level characteristics: age, sex, body mass index , smoking, physical activity, stress, fruit/vegetable intake, and alcohol consumption and the following community-level characteristics: community size, community growth and the Rurality Index. Among participants using blood pressure medication, SBP was associated with the following individual-level characteristics: age, sex, body mass index, diabetes, fruit/vegetable intake, alcohol intake and one community-level characteristic: community size. The significance and magnitude of these associations were modified by the use of blood pressure medication. Conclusion: The majority of the variability in blood pressure occurs at the individual-level. There are specific individual- and community-level factors that explain variability in blood pressure readings among communities. These results can be used to inform health promotion strategies to decrease mean levels of blood pressure among older adults.
Keywords: Blood pressure; Hypertension; Cardiovascular Health Awareness Program; community-level characteristics; systolic blood pressure; older adults